Selected aspects of Lycopodium annotinum L. sporulation - Śliwińska-Wyrzychowska, Anna; Bogdanowicz, Monika (Ecological Questions, 2012)
The conducted study aimed to show the differences in the process of sporulation at two populations of Lycopodium annotinum L. occurring within the governmental forests in the habitats: undisturbed and disturbed by economic treatments. The study was conducted in 2008-2011 in the southern part of the Krakowsko-Częstochowska Upland. It concerned the number of observations of sporophylls occurring during the year. There was also examined till which months within the year spores are released. The study also included observations of the lot of sporophylls which released the spores. Studies have shown that in the undisturbed habitat during the year there occurred 6 times more sporophylls than in the disturbed habitat. It was also observed that the period of their appearance in the undisturbed habitat was prolonged compared to literature data, and lasted until November 2008. Such a late appearance of sporophylls was not in the disturbed habitat, where the appearance of sporophylls was observed only until July 2008. However, only in the disturbed habitat there was observed occurrence of sporophylls in March 2009. In the undisturbed habitat spore release process lasted until October 2008, while in the disturbed one until September. In this habitat there was also observed that 28% of marked shoots with strobili died before the release of spores. This situation was not observed in the undisturbed habitat. The study also showed that in the both positions, after releasing the spores, all the shoots died within 3 years, however, in the disturbed habitat shoots died much faster than in the undisturbed one.